(untitled) (Research, Society and Development, 2022)
This study has the general objective of identifying the constitutive factors of the level of knowledge on the topic “Cryptocurrency and its form of taxation”. Specifically, it is intended to understand its acceptance and accounting, from the perspective of undergraduate students in Accounting Sciences, at a Federal University located in the interior of Mato Grosso do Sul. Therefore, based on descriptive statistics, we used quantitative data obtained through a questionnaire, prepared and applied to all students of the course. As a theoretical framework, we worked with researchers such as: Ackermann (2018), Chuen, Guo and Wang (2017), Ciaian et al. (2016), Lakomski-Laguerre and Desmedt (2015), Ramos (2017). Results obtained allowed, through analysis, the understanding of the evaluation averages of the variables of greatest significance: cryptocurrency presents high volatility; in Brazil there are no specific rules regarding the accounting treatment to be applied in operations that use Cryptocurrency; Accounting must consider that Cryptocurrency is, at the same time, an asset for those who carry it and a liability for those who issue it. Still, it was possible to highlight that acceptance is low and that the topic lacks regulation in the country. Finally, it is suggested that the subject deserves further research aimed at expanding knowledge on this subject.